Translation Shift Of Prepositional Phrase On Ice Age 4: Continental Drift And Its Subtitle - Lisnawati, Wahyu, Dra, Dwi Haryanti, M.Hum, Siti Fatimah, SPd, M. Hum (2013)
This research is translation shift. The aims of this research are to describe translation shift of prepositional phrase which is translated into Indonesian and to classify the equivalence translation of prepositional phrase found on Ice Age 4: Continental Drift. This research is descriptive qualitative research. In collecting data, the writer uses documentation by selecting and coding English sentences containing prepositional phrase in the Ice Age 4: Continental Drift movie manuscript. The writer finds two translation shifts, namely: structure shift and level shift. From 33 data the researcher finds 2 level shifts: (1) prepositional phrase is translated into verb 5 data or 15%, (2) prepositional phrase that is translated into noun 11 data or 33%. There are 2 shifts which belongs to category shift (structure shifts). There are 17 data or 52% from 33 data. They are: (1) prepositional phrase that is translated into verb phrase 3 data or 2%, (2) prepositional phrase that is translated into noun phrase 43% or 14 data. The writer finds prepositional phrase that is translated into prepositional phrase as the highest data. There are 100 data the prepositional phrase which translated into prepositional phrase was not analyzed because it doesn't have translation shift. The writer also classifies the equivalence and non equivalence translation. From 133 data, there are 128 data or 96% belongs to equivalence and 5 data or 4% belongs to non equivalence translation